Chemotactic signaling via carbohydrate phosphotransferase systems in Escherichia coli - Neumann-Pfeifer, Silke; Große, Karin; Sourjik, Victor (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Chemotaxis allows bacteria to follow gradients of nutrients, environmental stimuli, and signaling molecules, optimizing bacterial growth and survival. Escherichia coli has long served as a model of bacterial chemotaxis, and the signal processing by the core of its chemotaxis pathway is well understood. However, most of the research so far has focused on one branch of chemotactic signaling, in which ligands bind to periplasmic sensory domains of transmembrane chemoreceptors and induce a conformational change that is transduced across the membrane to regulate activity of the receptor-associated kinase CheA. Here we quantitatively characterize another, receptor-independent branch of chemotactic signaling that is linked to the sugar uptake through a large family of phosphotransferase systems (PTSs). Using in vivo characterization of intracellular signaling and protein interactions, we demonstrate that signals from cytoplasmic PTS components are transmitted directly to the sensory complexes formed by chemoreceptors, CheA and an adapter protein CheW. We further conclude that despite different modes of sensing, the PTS- and receptor-mediated signals have similar regulatory effects on the conformation of the sensory complexes. As a consequence, both types of signals become integrated and undergo common downstream processing including methylation-dependent adaptation. We propose that such mode of signaling is essential for efficient chemotaxis to PTS substrates and may be common to most bacteria.